Serological Evidence of Lyssaviruses among Bats on Southwestern Indian Ocean Islands. - Julien Mélade; Stewart McCulloch; Beza Ramasindrazana; Erwan Lagadec; Magali Turpin; Hervé Pascalis; Steven M Goodman; Wanda Markotter; Koussay Dellagi (PLoS ONE, 2016)
We provide serological evidence of lyssavirus circulation among bats on southwestern Indian Ocean (SWIO) islands. A total of 572 bats belonging to 22 species were collected on Anjouan, Mayotte, La Réunion, Mauritius, Mahé and Madagascar and screened by the Rapid Fluorescent Focus Inhibition Test for the presence of neutralising antibodies against the two main rabies related lyssaviruses circulating on the African continent: Duvenhage lyssavirus (DUVV) and Lagos bat lyssavirus (LBV), representing phylogroups I and II, respectively. A total of 97 and 42 sera were able to neutralise DUVV and LBV, respectively. No serum neutralised both DUVV and LBV but most DUVV-seropositive bats (n = 32/220) also neutralised European bat lyssavirus 1 (EBLV-1) but not Rabies lyssavirus (RABV), the prototypic lyssavirus of phylogroup I. These results highlight that lyssaviruses belonging to phylogroups I and II circulate in regional bat populations and that the putative phylogroup I lyssavirus is antigenically closer to DUVV and EBLV-1 than to RABV. Variation between bat species, roost sites and bioclimatic regions were observed. All brain samples tested by RT-PCR specific for lyssavirus RNA were negative.